Avaliação da eficácia da estufa de Pasteur como equipamento esterilizante em consultórios odontológicos do Distrito Central de Goiânia-GO - TAVARES, Solange do Socorro Fonseca (2005)
The aim of this analytical study was to evaluate the effectiveness of dry heat as a sterilizing equipment in dental offices with regard to: the packing of the load, the time and temperature used, the use of biological and chemical monitoring in the sterilization control as well as the performing of preventive maintenance. The data were obtained from 101 dental offices in the Central District of Goiânia, Goiás, Brazil, through the following procedures: use of check-list and interview; checking the temperature of the dry heat and performing the biological monitoring.The results showed that most of the people in charge of the article sterilization in dry heat performed it without the folowing proceedings proclaimed by Health Ministry: adequate package disposal, monitoring by accessory thermometer, performance of indicated cycles and accomplishment of preventive maintenance. The results also showed that the most significant intervening factors for the quality of sterilization were both the no accomplishment of chamber monitoring by accessory thermometer and time/temperature relationship indicated for sterilization cycle. In addition, dry heat was not effective for 46 (45,5%) dental offfices investigated, confirming other studies which concluded that dry heat is an equipment susceptible to sterilization failure and its effectiveness is close related to the accomplishment of the proclaimed loading and sterilization which depend on human action.